EUTHANASIA DITINJAU DARI HUKUM PIDANA DI INDONESIA - Ramanata Disurya (Fakultas Hukum Universitas IBA Palembang, 2020)
Abstract The emergence of pros and cons around the issue of euthanasia becomes a burden for law experts. Because, on the issue of